Marketing Communications Manajement for Kamasan Painting Art In The Karangasem Tourism Vilaage, Klungkung Regency - I Made Ananda Wiguna; I Nyoman Surpa Adisastra; Ida Ayu Made Galih Wulandari; Bagus Ade Tegar Prabawa (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2024)
Kamasan tourist village presents painting as a tourist destination. The painting art in question is Classical Wayang painting which originated during the reign of King Dalem Waturenggong (1386-1460). It can be said that the art of Classical Wayang Painting is a cultural heritage passed down from generation to generation which has its own characteristics, namely, displaying pieces of stories taken from the Sutasoma Book, such as the Mahabrata, Ramayana and Tantri stories. The colors in Kamasan Classical Wayang paintings are usually taken from natural colors, for example for white using crushed bones, for black using charcoal which is then mixed with adhesive so it can stick to the canvas. Kamasan Wayang paintings use two dimensions, length and width, there is no perspective, so that you can't see far up and down, while the objects painted are like wayang, flat without perspective or depth. The style of the Kamasan Classical Wayang painting is quite easy to recognize, the basic color is light brown, taken from limestone. For black, use soot. However, as time went by, painters used watercolors to make them more vibrant. This product is one element of the running of tourism activities, but along with this, the running of tourism activities cannot be separated from various strategies that have been carried out both by the government and cannot be separated from the role of the community in supporting the running of this tourist village. One of the strategies that has been implemented in developing the Kamasan tourist village is the marketing communications management using direct and indirect marketing communications with a marketing communications mix model. Marketing communication management carried out by Wayang Kamasan painters to increase sales by using a communication mix (marketing mix). Direct marketing communication activities carried out by Wayang Kamasan painters such as distributing business cards and word of mouth promotion. However, it seems that Wayang Kamasan painters are more dominant in marketing communications via social media such as Instagram, TikTok and websites. Kamasan Wayang Painter carries out marketing communications with a marketing communications mix with 4Ps, namely, (1) Product. There are several products being marketed, such as: 1. Wayang Kamasan paintings 2. Keben or sok kasi 3. Fans 4. Drinking bottles 5. T-shirts 6. Bags or tote bags 95 Apart from the products that Wayang Kamasan painters prepare, namely, (2) Price. Price is the amount of money charged for a product or service which can be interpreted as the price being the amount that consumers must pay when making a purchase. As a self-employed Wayang Kamasan painter, he sells products and services simultaneously at prices that can compete in the market. (3) Promotion is an activity to disseminate information. Kamasan Wayang Painters carry out direct and indirect promotions starting from distributing business cards, and promoting through social media such as Instagram, TikTok and providing a website for the shopping process. (4) Place, the fourth point in the marketing communication strategy for Wayang Kamasan painters is a place, used as a place to produce products as well as an art shop. For each art shop, Wayang Kamasan painters provide signboards to make it easier for potential customers to find the location they want to go to. Key Word: Communication Management, Marketing, for Kamasan Painting Art